Spotting Taboo in the SAMAN Novel: A Feminist Perspective in Digital Epoch - Wulandari, Fitriya Dessi; Salman Alade (Journal of Language Teaching Lingustics and Literature, 2025)
The novel "SAMAN" (1998) by Ayu Utami continues to provoke controversy due to its explicit portrayal of sexuality, which remains socially unacceptable even in today’s era. As a prominent figure of the "sastra wangi" generation, Ayu Utami garnered significant attention by highlighting real-life events that challenged societal norms and promoted freedom of expression during Indonesia's reformation period. Previous critics and studies had labeled the novel as vulgar and taboo. Furthermore, the digital era facilitates voices into this literary work from all people in unlimited space.  Building on its issues, this paper provides a systematic examination of sexual taboos from a feminist perspective and explores potential threats to future digital literacy. Methodologically, it relies on qualitative descriptions presented in the original novel and literary critiques. The analysis results in two insightful findings, first, through the lens of a feminist perspective, the analysis uncovers disparities in women's participation, rights, roles, and positions, while also candidly depicting taboos evident in certain descriptions and activities. Second, it reveals the description of the cultural context that portrays the story. The findings not only provide insights gained from this analysis but also offer valuable perspectives for fellow writers and contribute to the ongoing digital discourse in feminist literature on related issues.